Machiavelli on international relations - Machiavelli, Niccolò 1469-1527; Cesa, Marco 1958- (Oxford, United Kingdom Oxford University Press, 2014)
The importance of international politics in Niccolò Machiavelli's thought cannot be denied. Although the familiar ideas expressed in the Prince and the Discourses are obviously relevant, the Art of War, the History of Florence, the dispatches that he wrote during his diplomatic missions, several minor political writings, and the private letters contain a number of additional insights and observations that refine and enrich his views. This anthology gathers together for the first time all of Machiavelli's writing on international affairs.-- Publisher.
Chronology of Machiavelli's times and life -- Emperors, kings, and popes in Machiavelli's time -- Introduction -- Part I: A way of thinking and some basic assumptions -- A compelling logic -- Either, or. Speech concerning Pisa, Provisions for retaking Pisa ; What Duke Valentino will do. II Mission to Duke Valentino ; Reason guides analysis. Letter to Francesco Vettori, 29 April 1513 -- On human nature -- If men were all good. Prince XV, XVII, and XVIII ; Some men desire, whilst others fear. Discourses I, 37 and 5 ; Nations preserve for a long time the same character. Discourses III, 43 -- On times and affairs -- The world remains very much in the same condition. Discourses I, Introduction, 39, Discourses II, Introduction ; Times, the conditions of things, wisdom, and fortune. Letter to Giovan Battista Soderini, 13-21 September 1506 ; What Can, and cannot, be done about fortune. Prince XXV, Discourses II, 29 -- Part II: The international context : fear and self-help -- Survival and security -- Only force makes states keep their word. Words to be spoken on the law for appropriating money, after giving a little introduction and excuse ; Security is more important than glory. Life of Castruccio Castracani of Lucca ; All means are acceptable when the survival of the state is at stake. Discourses III, 41-2 ; The antagonism of opposing forces. Letter to Francesco Vettori, 20 June 1513 -- 'Fear is the greatest master' -- The Popes. Discourses I, 12, Florentine histories II, 10 ; France. An account of the affairs of France ; Spain. Letter to Francesco Vettori, 16 April 1514 ; Florence. Florentine histories V, 12-13 ; Naples. Florentine histories VIII, 19-22 ; Venice. Florentine histories I, 29 ; Milan. Florentine histories V, 5 -- Good laws and good armies -- The foundations of all states. Prince XII, Discourses III, 31 ; External threats and military organizations. Art of war II ; Military force is at the service of security. Art of war, Introduction and VII -- Part III: Domestic orders, disorders, and foreign affairs -- The great powers compared -- France. An account of the affairs of France ; The empire. Report on the affairs of Germany -- Domestic affairs and foreign affairs -- Location, growth, security, and laws. Discourses I, 1 ; Domestic divisions, forms of government, and expansion. Discourses I, 6 ; Domestic divisions and external enemies. Florentine histories, Introduction V, 4, II, 26, Discourses II, 25 -- Leaders and strategies -- Cosimo rules over a divided city. Florentine histories VII, 5-6 ; Duke Valentino establishes a new state. Prince VII ; Julius II temporizes. I Mission to the Court of Rome ; Ferdinand II rises in power and prestige. Prince XXI -- Republics and principalities -- A republic's foreign policy is reckless. Discourses I, 53 ; And slow. Discourses I, 34, II, 15 ; Both republics and principalities resort to fraud. Discourses II, 13 -- And end up subjugating those who invoke their help. Discourses II, 20 ; Republics are somewhat better equipped to adapt to the times. Discourses III, 9 ; And are somewhat more reliable allies. Discourses I, 59 ; Yet, republics are more predisposed to grow and expand, and are harsher masters. Discourses II, 2 -- Part IV: Foreign policy and international politics -- Preferences, opportunities, and constraints -- When will one act? Letter to Giovanni Ridolfi, 12 June 1506 ; Revisionist powers and international stability. Letter to Francesco Vettori, 10 August 1513 ; Goals change and necessity overrules intentions. Letter to Francesco Vettori, 10 August 1513, and Letter to Francesco Vettori, 26 August 1513 ; On molesting and being molested. Discourses II, 19 -- Dealing with threats -- Balancing against a great power is not easy at all. Discourses I, 33, III, 11 ; Having achieved security, states aim at more. Florentine histories V, 9-10, V, 17-22 ; Deciding to resist. Florentine histories V, 11 -- Engaging in expansion -- The Roman example. Discourses II, 1 ; A war of aggression. Florentine histories IV, 18-20 ; Taking a city by force may be counterproductive. Florentine histories VII, 30 ; Louis XII's mistakes. Prince III -- Neutrality and alliances -- Why neutrality is to be avoided. Prince XXI ; Alliances and the rise of Rome. Discourses II, 4 ; No way out. I Mission to France ; The risks of asymmetrical alliances. II Mission to Duke Valentino ; Allied misgivings. Florentine histories IV, 3-5, 13, 15 ; Coalitions are unreliable. Florentine histories VIII, 24-6 ; And litigious. Mission to Mantua on business with the Emperor -- Part V: History and analysis -- The Italian state system, 1444-1454. Florentine histories VI, 11-14, 17-27, 31-2 -- Entrapping an ally : France and Florence. III Mission to France -- What the Pope should do now. Letter to Francesco Vettori, 10 December 1514 -- Towards the Sack of Rome. Mission to Francesco Guicciardini at the Camp of the League of of Cognac.
Includes bibliographical references and index.
Keywords: Machiavelli, Niccolò -- 1469-1527.; International relations; World politics; International relations -- Philosophy; World politics -- Philosophy